Whole Exome Sequencing Identifies Genes Associated With Non-Obstructive Azoospermia - Zhang, Hongguo; Li, Wei; Jiang, Yuting; Li, Jia; Chen, Mucheng; Wang, Ruixue; Zhao, Jing; Peng, Zhiyu; Huang, Hui; Liu, Ruizhi (Frontiers in Genetics, 2022)
Background: Non-obstructive azoospermia (NOA) affects nearly 1% of men, however the landscape of the causative genes is largely unknown. Objective: To explore the genetic etiology which is the fundamental cause of NOA, a prospective case-control study and parental-proband trios linkage analysis were performed. Materials: 133 patients with clinicopathologic NOA and 343 fertile controls were recruited from a single large academic fertility center located in Northeast China, in addition eleven trio families were available and enrolled. Results: Whole exome sequencing based rare variant association study between the cases and controls was performed by means of the gene burden association testing. Linkage analysis on the trio families was also interrogated. Totally, 648 genes were identified to be associated with NOA (3 of which were previously reported), out of which 6 novel genes were found likely causative based on the linkage analysis in the trio families, and involved in the meiosis related network. Discussion and Conclusion: The 6 currently identified genes potentially account for a fraction (4.51%, 6 out of 133 patients) of the heritability of unidentified NOA, combining the six novel genes and the 3 previously reported genes would potentially account for an overall 7.52% (10 out of 133 patients) heritability of unidentified NOA in this study.